Práticas discursivas e relações afetivas na contemporaneidade: o caso dos verbos ficar e namorar no contexto do vestibular da UFRN - Araújo, Kassios Cley Costa de (2012)
This work is inserted to Applied Linguistic studies, concerned to the understanding that language is a social practice, bringing a qualitative research, discussing essential aspects that involve the subject and his/her discursive practice: signification and valuation. Due to this, we have elected as subject study, the sense and values attributed to the verbs make out and date searched on the articles written in the Vestibular 2005 process promoted by the Universidade Federal do Rio Grande do Norte (UFRN), that had the following instruction: In a relationship, is it better make out , just date , or, both, make out and date ? This research is based on the Circle of Bakhtin s dialogic theory, as well as in the notions of instability in the affective relationships nowadays and in the individualization and multiplicity of contemporaneous subjectivity. Those papers are important to analyze the meaning and values that the verbs make out and date present, nowadays, as expressions of an affective relationship and how this situation can interfere in the positions of subjectivity in a formal instance as a vestibular. Those textual productions reflect those relationships, confronting temporary ones, whose discuss is marked, in general, by social voices that evaluate to make out negatively and to date positively